Do Emotional Intelligence and Ethical Leadership Elevate Work Engagement? The Mediating Role of Psychological Capital - Primahesti Dyah Widowati; Aryana Satrya (Media Ekonomi dan Manajemen, 2023)
The level of employees’ work engagement can affect an organization's resilience amid business competition. However, banking employees are often faced with rigid working hours that can affect the level of work engagement of employees. This study aims to determine the role of emotional intelligence and ethical leadership in the work engagement of banking employees. Furthermore, this study also investigates the mediating role of psychological capital because it still requires further research. The sample involved in the study was 206 employees of conventional commercial banks in Indonesia. The structural equation modeling (SEM) analysis results show that emotional intelligence, ethical leadership, and psychological capital can affect work engagement. On the other hand, psychological capital partially mediates the influence of emotional and ethical leadership on work engagement. Therefore, the result of this study can strengthen the job demands-resources theory. To increase work engagement, a deeper understanding of emotional intelligence, ethical leadership, and psychological capital can help the banking sector retain employees, improve employee and organizational performance, and maintain a competitive advantage amid intense competition between banks in Indonesia.